Eriofiídeos (ACARINA: ERIOPHYIDAE) PREJUDICIAIS À BATATA-DOCE - Alves, Sérgio Batista; Calafiori, Maria Helena; Paschoal, Adilson Dias (REVISTA DE AGRICULTURA, 2016)
Eriofiídeos (ACARINA: ERIOPHYIDAE) PREJUDICIAIS À BATATA-DOCE